IMPLEMENTASI HALAL VALUE CHAIN BADAN USAHA MILIK PESANTREN (BUMPES) DI PONDOK PESANTREN TERPADU AL MUMTAZ GUNUNGKIDUL, YOGYAKARTA - Nurlina; Rahmanda Nur Azizah Dwi Septia Puteri (Fakultas Pertanian UST, 2023)
This study aims to determine the application of the halal value chain to goods and services at BUMPes Al Mumtaz. Respondents in this study were the daily task executors (plh) of caretakers of the Al Mumtaz integrated Islamic boarding school, directors of BUMPes, alumni and students as business actors. The data collection method in this study was carried out by interviews and then analyzed through data collection, data reduction, data display, and conclusion drawn). BUMPes Al Mumtaz has implemented an effective implementation of the halal value chain. This is determined in the formation of halal products that have been formed from a series of halal value chain activities in the production, distribution and consumption processes. The implementation of the halal value chain at BUMPes Al Mumtaz is realized by the existence of halal certification and labeling of the products produced. Halal certification and labeling are used to achieve a competitive advantage in order to create value for itsThis study aims to determine the application of the halal value chain to goods and services at BUMPes Al Mumtaz. Respondents in this study were the daily task executors (plh) of caretakers of the Al Mumtaz integrated Islamic boarding school, directors of BUMPes, alumni and students as business actors. The data collection method in this study was carried out by interviews and then analyzed through data collection, data reduction, data display, and conclusion drawn). BUMPes Al Mumtaz has implemented an effective implementation of the halal value chain. This is determined in the formation of halal products that have been formed from a series of halal value chain activities in the production, distribution and consumption processes. The implementation of the halal value chain at BUMPes Al Mumtaz is realized by the existence of halal certification and labeling of the products produced. Halal certification and labeling are used to achieve a competitive advantage in order to create value for its customers. Efforts that are manifested in a series of activities at BUMPes Al Mumtaz, namely planning material requirements, organizing the product manufacturing process, implementation in accordance with SOPs and control systems through routine evaluations that aim to increase excellence and create added value to the products produced by BUMPes Al Mumtaz